2013
DOI: 10.5424/sjar/2013112-3953
|View full text |Cite
|
Sign up to set email alerts
|

What comes first, origin or production method? An investigation into the relative importance of different attributes in the demand for eggs

Abstract: IntroductionConsumer food demand is not only driven by food product prices and consumer income as stated by traditional economic theory but increasingly by four classess of quality attributes for food products being those of sensory, health, process and convenience. Moreover, recent changes in consumer behavior have made consumers' demands more dynamic, complex and heterogeneous which are subject to cultural differences (Grunert, 2006). As a consequence, different consumer segments can be found in the food mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 55 publications
0
19
0
8
Order By: Relevance
“…The price was not included in this classification, consistent with studies by Grunert [4] and Lopez Galan et al [49]. These previous studies emphasised that food demand not only is driven by the price of a product and the income of the consumer, as stated by classic economic theory, but is also increasingly driven by more complex and heterogeneous attributes.…”
Section: Brand Knowledgementioning
confidence: 72%
“…The price was not included in this classification, consistent with studies by Grunert [4] and Lopez Galan et al [49]. These previous studies emphasised that food demand not only is driven by the price of a product and the income of the consumer, as stated by classic economic theory, but is also increasingly driven by more complex and heterogeneous attributes.…”
Section: Brand Knowledgementioning
confidence: 72%
“…In Denmark, consumers are ready to pay a significant price premium (58%) for organic eggs [38]. In Spain, 80% of consumers were willing to pay a price premium for organic eggs (EUR 0.85 for a six package) [39] and organic and local claims were complements for many of the consumers [13]. For Italian occasional organic consumers, locally produced foods (including eggs) are considered to have a higher quality level than organic, as the latter was found to be more distant [40].…”
Section: Consumers' Preference and Perception Of Organic Labelled Foodmentioning
confidence: 99%
“…Moreover, empirical studies on consumer preferences for several types of food quality labeling in Europe have indicated that the most prevalent food labeling schemes in Europe were also the most analyzed and found to provide the most value to European consumers. Most empirical studies conducted in Europe have focused on assessing consumer preferences for processed methods (organic, animal welfare) and the origin of production (regional, local) (Andersen, 2011;Aprile et al, 2012;Denver and Jensen, 2014;Gracia et al, 2014;López-Galán et al, 2013;Olesen et al, 2010;Pouta et al, 2010;Resano et al, 2012;Yangui et al, 2014 to name only few of the most recent ones). However, several empirical studies have also analyzed preferences for these two claims together with other attributes such as health (nutritional information, health claims) and environment/sustainability (food miles, footprint) (de-Magistris and Koistinen et al, 2013;Øvrum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%